Effect of Dimethyl Formamide (DMF) on Vanadium Reloading Over V-Ti SCR Catalyst - Song, Hao; Guo, Jiangmin; Liu, Shaojun; Zhang, Yu; Wu, Weihong; Zheng, Chenghang; Gao, Xiang (Frontiers in Energy Research, 2022)
Active components reloading is critical process for the catalyst regeneration, which is limited by the low adsorption capacity and unwilling distribution of desired components to the catalyst surface. Herein we demonstrated that with dimethyl formamide(DMF) modification and sequentially reloading of vanadium, the traditional V-Ti SCR catalyst, which uses vanadium as the active components and titanium as the carrier, showed the significantly improved DeNOx performance, owing to the increased adsorption capacity and desired distribution of vanadium. When the DMF concentration was 6%, the adsorption capacity of the promoted catalyst was 3.58 and 6.57 mg/g under vanadyl ion concentrations of 1.5 and 3 g/L, respectively, 135 and 147% higher than that of the original catalyst. Adsorption kinetics demonstrated that the pseudo-second-order kinetic model better describes the process by which vanadyl ions adsorb onto the catalyst. In addition, the adsorption equilibrium indicated that Langmuir model was a closer fit for the vanadyl ion adsorption to the promoted catalyst. After DMF modification, the vanadyl ions were first adsorbed onto the functional groups on the catalyst surface, substantially increasing the vanadium loading on the catalyst surface while limiting the increase in vanadium content within the interior of catalyst, which was conducive to enhancing the DeNOx activity and reducing the increase in the SO2/SO3 conversion. When the vanadium adsorption capacity was 3.5 mg/g, the increase in the DeNOx activity of the promoted catalyst was 68.1% higher than that of the original catalyst, whereas the increase in SO2/SO3 conversion was 28.9% lower than that of the original catalyst. Thus, in the regeneration of SCR catalysts vanadium initial concentration and loading could be reduced.